Communicative rationality of the exception - Carreño Donoso, Fernando Daniel (Re-presentaciones: Periodismo, comunicación y sociedad, 2018)
This paper intends to observe in a preliminary way the intimate relationship that exists between the notion of a state of exception, democracy and communication. The gamble focuses on showing the conceptual elements that, initially, would allow the argumentative plot to be constructed with respect to the communicative rationality of the exception, considering the agonal character of democracy. Finally, a brief reflection on the discourse and the media as possible devices of the exception is presented.